(untitled) (Applied Biological Research, 2015)
Single nucleotide polymorphisms (SNPs) represent stable, bi-allelic nucleotide variations that are distributed throughout the genome and are the most abundant genetic variation. The present study targeted SNP related molecular differentiation and phylogenetic relationship of Indian Helicoverpa armigera populations by using expressed sequence tags (ESTs) of partial cytochrome oxidase subunit I (COI). The phylogenetic evaluation clearly separated the northern and southern Indian populations of H. armigera with little admixtures of central Indian populations. The SNP mining also revealed two major clusters as that of phylogeny with a total of 11 potential SNPs, of which 10 were in reliable haplotypes. The potential SNPs were found to contain eight transitions, three transversions and no indels (insertions and deletions). Out of 38 sequences, 13 were haplotypes in which 4 were single haplotypes. In cluster 1, the reliable bi-allelic SNPs were observed at 97, 166 and 265 nucleotide positions; while they were at 411, 423, 522, 655 and 656 positions in cluster 2. The present study high lighted the genetic polymorphism and relationship of Indian H. armigera, besides confirming the long distance migration and gene flow between the geographic populations.